2018
DOI: 10.14419/ijet.v7i3.1.16788
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Identification of Maritime Boundary Alert System using GPS

Abstract: Global Positioning System (GPS) is being used more and more for a wide range of applications. This is a reliable position, navigation for end-users of anywhere in the world or around the globe, on any weather, day or night. The synchronization benefit gives that the GPS has three segments: space, control and client GPS has turned into a broadly utilized route apparatus over the world and turn into a helpful instrument for mapping, overviews, business, logical utilizations, checking and diversion has gone. As i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Liu et al [2] work with the calculation of the distance of an object from the camera using binocular vision. Using two cameras, an object's position from both the cameras would be slightly different from the other.…”
Section: Literature Surveymentioning
confidence: 99%
“…Liu et al [2] work with the calculation of the distance of an object from the camera using binocular vision. Using two cameras, an object's position from both the cameras would be slightly different from the other.…”
Section: Literature Surveymentioning
confidence: 99%
“…The 2007 CARE -European Road Accident Database Study [4], [5] found that each year in EU member states, 43,000 people die and 1.8 million suffer injuries at a cost of €160 billion.About 3% of the global GDP, or $1 trillion US, is VANET, a subset of MANET (Mobile Ad Hoc Network), is a mobile network that employs moving cars as network nodes to enable communication between the moving vehicle and the surrounding fixed infrastructure [13]. Because it offers a way to gather freely obtained traffic information and sense physical properties linked to exchanging traffic information, VANET is also known as VSN (Vehicle Sensor Network) [14], [15].…”
Section: Introductionmentioning
confidence: 99%